Influência da mescla de resinas uréia formaldeído e difenilmetano 4,4’- diisocianato (MDI) nas propriedades mecânicas e emissão de formaldeído de painéis de madeira aglomerada - Carneiro, Taís de Lima Alves (Universidade Federal de São Carlos, 2017)
Several studies take place in order to reduce and even extinguish formaldehyde use in its various applications. This is due to its classification as a carcinogen according to the International Agency for Research on Cancer (IARC). Most of the formaldehyde production is destined to obtain amino resins. After the synthesis of these resins formaldehyde being fully reacted is no longer found free and therefore presents no carcinogenicity risk. However, these amine resins when used as a binder in wood composites, can release formaldehyde. MDP (medium density particleboard) panels were produced on laboratory scale using as binder urea formaldehyde resin and the mixture of urea formaldehyde resin with MDI (diphenylmethane 4,4 'diisocyanate). The MDI partially replaced the formaldehyde urea resin at concentrations of 10%, 20% and 30% in order to evaluate in these mixtures the influence on perpendicular tensile strength, also known as internal adhesion, in determining swelling and water absorption after immersion For 2 hours and 24 hours, formaldehyde emission and flexural strength. The resin blend was effective in reducing the emission of formaldehyde and an increase in the mechanical properties was possible. Among the conditions evaluated, condition 3, with 20% of methyl 4,4 'diisocyanate (MDI) and 80% of formaldehyde urea, presented the most satisfactory results in relation to cost-benefit. In condition 3, the formaldehyde emission was reduced by 75% and the results of the mechanical properties evaluated were satisfactory. In all analyzes, an increase was observed in relation to the panels produced with urea formaldehyde resin.
Influence of the mixture of formaldehyde and diphenylmethane resins 4,4'- diisocyalate (MDI) on the mechanical properties and formaldehyde emission of agglomerated wood panels
Keywords: Emissão de formaldeído; Painéis de madeira aglomerada; MDI; Uréia formaldeído; Formaldehyde emission; Agglomerated Wood panels; Urea-formaldehyde; CIENCIAS EXATAS E DA TERRA::QUIMICA